Effect of different repair techniques on the accuracy of repositioning the fractured denture base - Goiato, Marcelo Coelho [UNESP]; Pesqueira, Aldieris Alves [UNESP]; Vedovatto, Eduardo [UNESP]; Santos, Daniela Micheline dos [UNESP]; Gennari Filho, Humberto [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
Objective:This study investigated the efficacy of different techniques for the union of fragments of a denture before repair and on the accuracy of the reposition.Materials and methods:For this study, 20 maxillary dentures made with Lucitone 550 heat-cured resin were used. Points were determined with a scanner on the cusp of the teeth, as a measurement of the segments. After digitisation, each model was exported to the AUTOCAD R 14 program and two-dimensional measurements of the distances between the marked points were made. After the initial analysis, the dentures were fractured into two segments using an impact test machine. For the repair, maxillary dentures were divided into two groups; in the first, the repair was carried out using Kerr's sticky wax and in the second group, Super Bonder was used to join the fragments, with subsequent inclusion of DENTSPLY((R)) Repair Material resin. After the repair, the points of the maxillary dentures were measured again. The numerical values obtained were tabulated to compare the measurements before fracture and after the repair. For statistical analysis, analysis of variance was employed, using a single factor and double factor, followed by the Tukey test with a reliability of 95%.Results:The results demonstrated a statistically significant difference between the materials used to join the dentures for repair, where the dentures were joined with sticky wax presented a larger variation in the distances between the points.Conclusion:The variation in distances between the points is influenced by the agent of repair.
Keywords: repair; denture complete; dimensional stability; prostheses